Noah the narwhal : a tale of downs and ups - Klausner, Judith, 1986- (Dancing Mantis Press, 2017)
"Noah the Narwhal has good days, when he is productive and social, and pain days, when he needs to rest. His friends and family can find it difficult to handle the unpredictability. Can they come to see that having him in their lives is absolutely worth it?"